Vascular Health in American Football Players: Cardiovascular Risk Increased in Division III Players. (24th January 2016) - Feairheller, Deborah L.; Aichele, Kristin R.; Oakman, Joyann E.; Neal, Michael P.; Cromwell, Christina M.; Lenzo, Jessica M.; Perez, Avery N.; Bye, Naomi L.; Santaniello, Erica L.; Hill, Jessica A.; Evans, Rachel C.; Thiele, Karla A.; et al.
Abstract : Studies report that football players have high blood pressure (BP) and increased cardiovascular risk. There are over 70, 000 NCAA football players and 450 Division III schools sponsor football programs, yet limited research exists on vascular health of athletes. This study aimed to compare vascular and cardiovascular health measures between football players and nonathlete controls. Twenty-three athletes and 19 nonathletes participated. Vascular health measures included flow-mediated dilation (FMD) and carotid artery intima-media thickness (IMT). Cardiovascular measures included clinic and 24 hr BP levels, body composition, V O 2 max, and fasting glucose/cholesterol levels. Compared to controls, football players had a worse vascular and cardiovascular profile. Football players had thicker carotid artery IMT (0.49 ± 0.06 mm versus 0.46 ± 0.07 mm) and larger brachial artery diameter during FMD (4.3 ± 0.5 mm versus 3.7 ± 0.6 mm), but no difference in percent FMD. Systolic BP was significantly higher in football players at all measurements: resting (128.2 ± 6.4 mmHg versus 122.4 ± 6.8 mmHg), submaximal exercise (150.4 ± 18.8 mmHg versus 137.3 ± 9.5 mmHg), maximal exercise (211.3 ± 25.9 mmHg versus 191.4 ± 19.2 mmHg), and 24-hour BP (124.9 ± 6.3 mmHg versus 109.8 ± 3.7 mmHg). Football players also had higher fasting glucose (91.6 ± 6.5 mg/dL versus 86.6 ± 5.8 mg/dL), lower HDL (36.5 ± 11.2 mg/dL versus 47.1 ± 14.8 mg/dL), and higher body fat percentage (29.2 ± 7.9 % versus 23.2 ± 7.0 %). Division III collegiate football players remain an understudied population and may be at increased cardiovascular risk.